2001
DOI: 10.1097/00005344-200112000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Inhibits Coronary Endothelial Cell Calcium Entry and Coronary Artery Relaxation

Abstract: Hyperinsulinemia is closely related to coronary artery disease. Endothelial cells are important for the control of vascular tone, and dysfunction of endothelial cells has been implicated in coronary artery disease. The direct effects of insulin on coronary endothelial cells are nonetheless unknown. In this study, the acute effects of high-dose insulin were investigated on agonist-induced intracellular Ca(2+) concentration ([Ca(2+)](i)) in porcine coronary endothelial cells and coronary relaxation. Bradykinin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…More specifically, many ECs normally respond to agonist stimulation in a biphasic manner consisting of an initial transient peak rise in [Ca 2C ] i followed by a prolonged sustained phase, but in many cardiovascular disease states the sustained phase may be lost (Salameh & Dhein 1998, Kimura et al 2001, Kuroda et al 2001, Tran et al 2001. Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, many ECs normally respond to agonist stimulation in a biphasic manner consisting of an initial transient peak rise in [Ca 2C ] i followed by a prolonged sustained phase, but in many cardiovascular disease states the sustained phase may be lost (Salameh & Dhein 1998, Kimura et al 2001, Kuroda et al 2001, Tran et al 2001. Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that PMC exert inhibitory action on the Ca 2+ sequestration mechanisms in the ER, thus compromising their ability or capacity to buffer the entering Ca 2+ (9, 10). Indeed, cyclopiazonic acid (CPA), which is a modified ATA and also a potent inhibitor of sarcoplamic reticulum (SR) Ca 2+ -ATPase, also caused slow endothelium-dependent relaxation (7,11) via raising cytosolic Ca 2+ levels in cultured vascular endothelial cells (5,12,13). While CPA is a non-selective inhibitor for various SERCA isoforms (14, 15), PMC, being more selective for its action on endothelial cells, may be more selective for SERCA3, the major isoform present in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%